Recent advances in toxoplasma gondii immunotherapeutics - Lim, S.S.Y.; Othman, R.Y. (The Korean Journal of Parasitology, 2014)
Toxoplasmosis is an opportunistic infection caused by the protozoan parasite Toxoplasma gondii. T gondii is widespread globally and causes severe diseases in individuals with impaired immune defences as well as congenitally infected infants. The high prevalence rate in some parts of the world such as South America and Africa, coupled with the current drug treatments that trigger hypersensitivity reactions, makes the development of immunotherapeutics intervention a highly important research priority. Immunotherapeutics strategies could either be a vaccine which would confer a pre-emptive immunity to infection, or passive immunization in cases of disease recrudescence or recurrent clinical diseases. As the severity of clinical manifestations is often greater in developing nations, the development of well-tolerated and safe immunotherapeutics becomes not only a scientific pursuit, but a humanitarian enterprise. In the last few years, much progress has been made in vaccine research with new antigens, novel adjuvants, and innovative vaccine delivery such as nanoparticles and antigen encapsulations. A literature search over the past 5 years showed that most experimental studies were focused on DNA vaccination at 52%, followed by protein vaccination which formed 36% of the studies, live attenuated vaccinations at 9%, and heterologous vaccination at 3%; while there were few on passive immunization. Recent progress in studies on vaccination, passive immunization, as well as insights gained from these immunotherapeutics is highlighted in this review.